Representasi Pendidikan Transformasif Melalui Kearifan Lokal: Inovasi Pedagogis Berbasis Narasi Tradisional Masyarakat Banyuwangi - Hikmah, Siti Nur Afifatul; Nurhayati, Aini (Indo-MathEdu Intellectuals Journal, 2025)
Banyuwangi as a district in the east of Java Island has a very rich cultural heritage of traditional dances such as Gandrung, traditional rituals, folklore, and so on. This pedagogical innovation is relevant in the context of education that connects theory with real practice while strengthening cultural roots. By integrating folk tales, songs, and traditional rituals into the learning process. The purpose of this study is to analyze the form of implementation, strategy, and role of values ​​contained in transformative education through the local wisdom of the Banyuwangi community. This researcher uses a qualitative approach with a type of field research based on cultural studies, with data collection techniques in the form of observation, field notes, structured interviews and document studies. The data analysis technique used is Miles Huberman. This study found that there is a relationship between transformative education based on the local wisdom of the Banyuwangi community